Australian Chinese parents' language attitudes and practices relating to their children's bilingual development prior to school. (June 2014) - Hu, Jiangbo; Torr, Jane; Whiteman, Peter
This article reports on a deep investigation of five Australian Chinese families regarding their preschool-aged children's bilingual experiences and development. Each family was visited 3 to 5 times by the first author. The mothers were interviewed about their attitudes toward their child's bilingualism and their practices to promote it. A detailed observation lasting 4 to 5 hours was undertaken of each family to record the interaction between parents and children. The findings suggest that Chinese parents have positive attitudes toward bilingualism for pragmatic reasons, such as future career success and ease of communication with family members. Yet they also expressed concern that their child's development of the home language would have a negative effect on their child's English language development. Observations demonstrated that parents' interactions with their children were frequently playful and informal, and English language was frequently used. Many of the materials parents provided to support their child's home language, such as picture books and DVDs, were actually rooted in English culture. These findings suggest there is room for Chinese parents to increase their awareness of bilingual development in children, including the relationship between first and second language development and strategies for facilitating their children's learning.